Unitary subgroups of commutative group algebras of characteristic two - Laver, V.; Balogh, Z. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.552.7 Let FG be the group algebra of a finite 2-group G over a finite field F of characteristic two and an involution which arises from G. The -unitary subgroup of FG, denoted by V_(FG), is defined to be the set of all normalized units u satisfying the property u^=u^-1. In this paper we establish the order of V_(FG) for all involutions which arise from G, where G is a finite cyclic 2-group and show that all -unitary subgroups of FG are not isomorphic.